Field Study of Car Discs Brake Temperature at Highway Exit Using Infrared Thermography - Kannan, Natesh; Ismon, Maznan (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study investigates the thermal performance of Proton car disc brakes under real-world driving conditions on the PLUS Highway using infrared thermography. The primary objective was to capture and record the operating temperature of Proton car disc brakes using infrared thermography, while also analyzing the temperature distribution and thermal behavior under real-world highway driving conditions, including frequent braking events at toll plazas. Using the FLIR T640 infrared thermography camera, real-time temperature data were collected at various times of the day, considering the impact of environmental factors such as ambient temperature and humidity. The results revealed significant temperature variations, with higher temperatures recorded during peak traffic, raising concerns about brake fade, disc warping, and potential wear. The study emphasizes the importance of thermal management in braking systems, proposing design improvements to enhance heat dissipation and reduce wear. This research provides valuable insights into the behavior of Proton car disc brakes in highway conditions and contributes to improving vehicle safety and brake system performance. Additionally, the study highlights the need for further research into alternative materials and cooling techniques for automotive braking systems to address the challenges posed by heat accumulation.